Ragam Pemaknaan Jihad dalam Kitab Fatḥ al-Bârî dan Irshâd al-Sârî - Muna, Moh. Nailul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2017)
This paper aims to provide new meanings on jihad in the ?adîth. From many explanations of jihad, it is rarely found the study of jihad in the perspective of explanatory books of ?adîth (shar?), which is actually the interpretation of the main Hadith books. This study employs the books of shar? in comparative framework, that is to compare the meanings of jihad presented in the book of Fat? al-Barî and Irshâd al-Sârî, which are considered as the most representative book to explain Sa?î? al-Bukhârî. Based on reading those two books, it was found that jihad is not similar with war, and also does not only mean to fight unbelievers. Besides, it also means to fight against demons and lust in every single Muslim soul. The last meaning argues the incompatibility understanding of jihad as a war, as it is common in social perception. By tracking the socio-historical side, it is explained in both books that the law of jihad are far? ‘ayn or far? kifâyah, which is based on the contextual situation.",